Acceptance of multiple injectable vaccines in a single immunization visit in The Gambia pre and post introduction of inactivated polio vaccine. Issue 41 (22nd September 2016) - Idoko, Olubukola T.; Hampton, Lee M.; Mboizi, Robert B.; Agbla, Schadrac C.; Wallace, Aaron S.; Harris, Jennifer B.; Sowe, Dawda; Ehlman, Daniel C.; Kampmann, Beate; Ota, Martin O.; Hyde, Terri B.
Highlights: Administration of multiple injectable vaccines during a single visit is increasing necessary. Administering multiple injections may not always be acceptable to caregivers and vaccinators. 9.9% of vaccinators and 35.7% of caregivers expressed concerns regarding multiple injections. Nevertheless all children surveyed received the required vaccines when vaccines were available. Abstract: Background: As the World Health Organization (WHO) currently recommends that children be protected against 11 different pathogens, it is becoming increasingly necessary to administer multiple injectable vaccines during a single immunization visit. In this study we assess Gambian healthcare providers' and infant caregivers' attitudes and practices related to the administration of multiple injectable vaccines to a child at a single immunization visit before and after the 2015 introduction of inactivated polio vaccine (IPV). IPV introduction increased the number of injectable vaccines recommended for the 4-month immunization visit from two to three in The Gambia. Methods: We conducted a cross-sectional questionnaire-based survey before and after the introduction of IPV at 4 months of age in a representative sample of all health facilities providing immunizations in The Gambia. Healthcare providers who administer vaccines at the selected health facilities and caregivers who brought infants for their 4 month immunization visit were surveyed. Findings: Prior to IPV introduction, 9.9% of healthcare providers and 35.7% of infant caregivers expressed concern about a child receiving more than 2 injections in a single visit. Nevertheless, 98.8% and 90.9% of infants received all required vaccinations for the visit before and after IPV introduction, respectively. The only reason why vaccines were not received was vaccine stock-outs. Infant caregivers generally agreed that vaccinators could be trusted to provide accurate information regarding the number of vaccines that a child needed. Conclusion: Healthcare providers and infant caregivers in this resource limited setting accepted an increase in the number of injectable vaccines administered at a single visit even though some expressed concerns about the increase.